PEWARTAAN FATWA MENURUT ENAKMEN PENTADBIRAN PERUNDANGAN ISLAM SELANGOR 1989 DAN PENGUATKUASAANNYA - Abdul Wahab, Mazni (Jurnal Syariah, 2019)
This article generally attempts to clarify the process of gazetting fatwa in the state of Selangor and measuring to what extent the gazetted fatwa are binding to the Muslim community. Several issues regarding the enforcement of fatwa is also briefly discussed.